When Is Accreting/Deleting Texture Seen as In Front? Interpretation of Depth From Texture Motion. (July 2018) - Tanrıkulu, Ömer Dağlar; Froyen, Vicky; Feldman, Jacob; Singh, Manish
Standard accounts of accretion/deletion of texture treat it as a definite cue to depth ordering: The accreting/deleting surface is interpreted as being behind the adjoining surface. Froyen, Feldman, and Singh showed that accretion/deletion can also, under certain circumstances, be perceived as a 3D column rotating in front, with the accretion/deletion explained by self-occlusion. These displays differ from traditional accretion/deletion displays in a number of factors, including the presence of figure/ground cues, accretion/deletion on both sides of boundaries, and in the number of distinct regions. In a series of experiments, we systematically manipulated each of these factors in order to determine what factors are actually instrumental in creating the rotating column (accretion/deletion in front) interpretation. In Experiment 1, the width of each region was kept fixed while manipulating the number of regions, and in Experiment 2, the width of the overall display was kept fixed. Observers indicated which set of regions they perceived to be in front. In both experiments, accreting/deleting regions were most likely to be seen in front when geometric figural cues favored a figural interpretation and when textural motion was introduced in all regions (rather than on just one side of each boundary). The number of regions had a relatively small effect (although this effect was larger in Experiment 2). These findings indicate that the geometry of the occluding contour is a critical factor in the interpretation of accretion/deleting, and future models of 3D interpretation involving accretion/deletion must include contour geometry as a key component.